Consumerisation of IT: Intersection of development streams of business and personal IT - Petrović Marijana; Sakal Marton (Strategic Management, 2025)
Background: In the age of IT consumerisation, private owned IT artifacts are increasingly used for business purposes. Management's approval is not required, but various approaches are used to create effective management strategies. Purpose: The historical development trends of business and personal ICT are examined in the paper to understand their intersection - IT consumerisation. Study design/methodology/approach: The paper provides a preliminary research assessment. The informative outcomes drawn from diverse perspectives and the comprehensive nature of 'gray literature' should serve as guidance for the direction, adjustments, and modifications of future research. Findings/conclusions: A number of technological and market factors have led to the consumerisation of IT. As a spinout from business IT, personal IT has had a feedback effect on it: the proliferation of computers and mobile devices on the consumer market, combined with affordable Internet-related resources, not only changed personal IT usage patterns, but also redefined the expectations that users have for enterprise software. In order to create an effective IT consumerisation management strategy, it is imperative to understand them. Limitations/future research: The paper is a starting point for future empirical research in the field of IT consumerisation, and as such, may be amended according to new knowledge that is obtained subsequently.